PTU-072 Evaluation of the Impact of different Commercially available DNA Extraction Kits and Laboratories for Assessing Bacterial Community Structure in Faecal Samples – Implications for IBD Research. (4th June 2013) - Kennedy, N; Walker, A; Berry, S; Duncan, S; Farquharson, F; Louis, P; Satsangi, J; Flint, H; Lees, C; Hold, G
Abstract : Introduction: Determining faecal sample bacterial community structure through sequence analysis of DNA has become a very important facet of inflammatory bowel disease (IBD) research. The possible impact of different commercially available DNA extraction kits and the influence of different lab environments on the data generated has however received relatively little attention. The study compared bacterial communities in faecal samples extracted using commercial DNA kits in established gastrointestinal research laboratories. Methods: Faecal samples from 2 healthy volunteers and 2 IBD patients with relapse were investigated. DNA extraction was undertaken using MoBio and Fastprep DNA extraction kits in two established labs. Two protocols were followed for processing samples using the Fastprep kit. Each DNA sample was then split and an aliquot transferred to the other lab. Pyrosequencing PCR of bacterial 16S rRNA genes was performed in both labs on all samples. Quantitative PCR analysis (q-PCR) to validate sequencing data was also performed. Hierarchical clustering was done using the Jaccard and Theta Yue & Clayton similarity coefficients on the pyrosequencing data. Results: DNA extracted using methods FastPrep1, FastPrep2 and the MoBio kit yielded median DNA concentrations of 476 (interquartile range 290–518), 453 (IQR 228–689) and 22 (IQR 9–36) ng/µL respectively. Those obtained with MoBio were significantly lower than FastPrep (p < 0.0001). Hierarchical clustering of sequence data revealed four clusters, with samples clustering by patient. Within each patient cluster, samples clustered by DNA extraction kit. Linear modelling of the effect of patient and kit on relative abundance of common bacterial classes revealed significant differences between MoBio and FastPrep. Ruminococcaceae and Bacteroidetes were significantly increased in MoBio extracted samples, while Lachnospiraceae and Enterobacteriaceae were significantly reduced (p < 0.05 in each case). Q-PCR revealed good correlation with sequencing data, with R2 of 0.94, 0.82, 0.69 and 0.57 for Enterobacteriaceae, Bacteroides, Ruminococcaceae and Lachnospiraceae respectively. Conclusion: This study demonstrates significant differences in DNA yield and bacterial DNA composition seen when comparing DNA extracted from the same faecal sample with different extraction kits. This highlights the importance of ensuring that all samples to be analysed together are prepared with the same DNA extraction method, and the need for caution when comparing studies that have used different methods. Disclosure of Interest: None Declared